Usefulness of Bone Marrow and Pattern of Morphological lesions in Patients of Chronic Renal Disease - Naseem, Lubna; Naseem, Lubna; Hassan, Khalid (International Journal of Pathology, 2018)
Objective: Bone marrow examinations provide useful insight into various etiological features of altered haematologyand pattern of morphological lesions in patients of Chronic Renal Disease.Materials and Methods: A total of 58 patients with documented Chronic Renal Disease, who underwent bonemarrow biopsy for various indications, were included. Their clinical data, peripheral blood and bone marrow findingswere analyzed.Results: In a total of 58 cases studied, age ranged from 15-80 years. There were 74%males and 26% females.Male to female ratio was 2.8:1. The most common among the clinical features was pallor seen in 91% of cases.Bone marrow biopsy revealed Anemia of chronic disease in 44.8%,Bone marrow hypoplasia in 37.9%, Iron deficiencyin 5.1%, Multiple myeloma in 6.9%, Excessive peripheral platelet destruction in 13.7%, Chronic renal diseasewith known NHL and hemolysis in 1.7% of cases.Conclusion: Bone marrow aspiration and trephine biopsies were found useful in investigating various hematologicalabnormalities in patients presenting with Chronic Renal Disease.